Flyte [compact disc, unabridged] - Sage, Angie (Sage, Angie. Septimus Heap, 2015)
It's been a year since Septimus Heap discovered his real family and true calling to be a wizard. As apprentice to extra ordinary wizard Marcia Overstrand, he is learning the fine arts of conjurations, charms, and other Magyk, while Jenna is adapting to life as the princess and enjoying the freedom of the castle. But there is something sinister at work. Marcia is constantly trailed by a menacing Darke Shadow, and Septimus's brother Simon seems bent on a revenge no one understands. Why is the Darke Magyk still lingering? Bringing fantasy to new heights, Angie Sage continues the journey of Septimus Heap with her trademark humor and all of the clever details readers have come to love.